Chronic acquired radial head dislocations associated with ulnar bowing in children. Report of three cases - (:unkn) unknown (SPRINGER, 2007)
The most common cause of chronic radial head dislocations is Monteggia lesions. Although acute, Monteggia fractures in children are easy to treat; complex reconstruction techniques may be required to reduce and stabilize chronic radial head dislocations. Early, accurate diagnosis and appropriate treatment remain the key factors for successful results in Monteggia or equivalent lesions in children.
Keywords: Monteggia lesions; radial head; dislocation; ulnar osteotomy; MONTEGGIA LESIONS; OPEN REDUCTION; FRACTURES; OSTEOTOMY